A systematic literature review on the effects of synthesis conditions to the physicochemical properties of activated carbons and their performance in methylene blue adsorption - Nasaruddin, Ricca Rahman (Malaysian Catalysis-An International Journal, 2022)
This systematic literature review (SLR) describes the trend of study in activated carbons (ACs) from various biomass sources, specifically coconut shell, rice husks, and bamboo, for the adsorption of methylene blue (MB). Data acquisition and extraction from online databases were performed to review and discusses the effects of the synthesis parameters (i.e., carbonization temperature and holding time) to the physicochemical properties of the synthesized ACs (i.e., surface area, pore volume) and the effects of physicochemical properties to the MD adsorption. The SLR shows that the carbonization temperatures significantly affect the surface area and pore volume of ACs synthesized from coconut shells and rice husks, while ACs synthesized from bamboo were significantly influenced by the holding time. MB adsorption by ACs from all three biomasses increased with the increasing surface area and pore volume. This SLR could be a guideline to the synthesis ACs from biomass for the removal of dye in wastewater.